Correlation between grain size variation and hydrogen embrittlement in a cost-effective Fe40Mn40Ni10Cr10 austenitic medium entropy alloy. (15th February 2023) - Kim, Dong-Han; Moallemi, Mohammad; Kim, Kyung-Shik; Cho, Hyung-Jun; Kim, Sung-Joon
Abstract: The effect of grain size variation (11 μm, 34 μm) on the hydrogen-induced tensile properties degradation of a Co-free cost-effective Fe40 Mn40 Ni10 Cr10 austenitic medium entropy alloy was investigated using a slow strain rate test. Despite improving both strength and ductility with decreasing the grain size in non-charged conditions, the fine-grain alloy showed a higher relative elongation loss after electro-chemical hydrogen charging. The larger ductility loss in the fine-grain alloy was ascribed to the fast propagation rate of major intergranular cracks and the drastic strain hardening rate drop of the alloy under hydrogen charging. The Schmid factor analysis showed that the enhanced dislocation activity in the fine-grain alloy compared with coarse-grain one was responsible for rapid hydrogen transfer to the grain boundaries, fast dislocation pile-up behind the grain boundaries, and, consequently, more severe hydrogen embrittlement. The significant stress concentration near the grain boundaries and fast intergranular crack propagation were recognized to be the main reason for premature fracture in fine-grain alloy. Highlights: The elongation loss under hydrogen charging was higher in fine-grained Fe40 Mn40 Ni10 Cr10 alloy than the coarse-grained one. The propagation route of hydrogen-induced cracks was different in fine-grained and coarse-grained specimens. More drastic elongation loss in the fine-grained alloy was related to developing major cracks and dislocations activity.